22.1k views
5 votes
Need help with this question ​

Need help with this question ​-example-1
User Kim
by
5.5k points

2 Answers

4 votes


- 2 {x}^(5) {y}^(7)

Solution:


- 2 {x}^(3) {y}^(4) {x}^(2) {y}^(3)


= 2 {x}^((3 + 2)) {y}^((4 + 3))


= - 2 {x}^(5) {y}^(7)


{\boxed{\blue{\textsf{Some Important Laws of Indices}}}}


{a}^(n).{a}^(m)={a}^((n + m))


{a}^(-1)=(1)/(a)


\frac{{a}^(n)}{ {a}^(m)}={a}^((n-m))


{({a}^(c))}^(b)={a}^(b* c)={a}^(bc)


{a}^{(1)/(x)}=\sqrt[x]{a}


a^0 = 1


[\text{Where all variables are real and greater than 0}]

User LondonPhantom
by
6.0k points
3 votes

Answer:


- 2 {x}^(5) {y}^(7)

Last option is correct.

Explanation:


- 2 {x}^(3) {y}^(4) {x}^(2) {y}^(3)

Multiply the terms with the same base by adding their exponents


- 2 {x}^(3 + 2) {y}^(4 + 3)

Add the numbers


- 2 {x}^(5) {y}^(7)

Hope this helps..

Best regards!

User Danmux
by
6.0k points